Pulsatilla bohemica (Skalický) Tzvelev (Ranunculaceae Juss.) на Кіровоградщині: біоморфологічні особливості, стан і структура ценопопуляцій - Barmak, I.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
A case study peculiarities of ontomorphogenetic, of conditions and the structure of populations of Pulsatilla bohemica (Skalickỳ) Tzvelev. Populations of the normal type with the absolute maximum on generative plants. Reactions of P. bohemica to stress situations were studied. The recommendations for protection of this species have been made.